Análisis ético de la carta encíclica: Caritas in veritate (2016)
The Caritas in Veritate encyclical was released on June 29, 2009, under Pope Benedict XVI. Originated as a tribute and continuation of the teachings of Paul VI outlined in the encyclical letter Populorum Progressio, it addresses the integral human development of peoples in charity and truth. On the occasion of the 40th anniversary of publication of this last encyclical, he wanted it to be ready for 2007, but the intense work required did not allowed its issuance; until two years later. The reception of the letter was quite positive, of which attest to two very eloquent facts: the message of support to the encyclical, entitled Doing the Truth in Love, signed by 56 personalities from the American evangelical Protestant world; and consideration that appeared in The New York Times, according to which both progressives and conservatives were challenged by the letter to "rethink their positions." (Blanco, 2009). Pope Benedict was even suggested as a candidate for the Nobel Prize in Economics “for having been the only one who has linked the economic crisis with the demographic crisis and the declining birthrate” (Blanco, 2009).